FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP HUBUNGAN BADAN PENGEMBANGAN WILAYAH SURAMADU DENGAN LEMBAGA PERENCANAAN KABUPATEN DI MADURA BERDASARKAN PERSEPSI STAKEHOLDERS - , R. SUFIA KURNIATI, Ir. Leksono Probo Subanu, MURP., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The formation of local development Authority Board is one strategy of the Central Government in local development. Following the case of Batam Authority, the Central Government formed is aimed Board of Suramadu Development (BPWS). This BPWS to optimize industrialized development in Madura. Batam Authority was formed in 1971, when Indonesia followed centralistic-new order government systems, while BPWS was formed in 2008 when the governmental systems of Indonesia had been decentralized. The relationship between boards formed by the Central Government and boards formed by Local Autonomy is crucial. This study aimed at: (1) Describing the relationship between BPWS and planning board of regency in Madura as perceived by stakeholders